Irrigação como fortalecimento da agricultura familiar do município de Salto do Lontra-PR - Ostroski, Diane Aparecida (2019)
This trial aimed at contributing to understand irrigation as a relevant tool for the rural development of irrigating familiar famers in Salto do Lontra, southwestern Paraná, and emphasize organizational, institutional, social and economic issues driven by this technology. The first analysis identified the participation of institutional and organizational environments of the municipality in dissemination and strengthening of irrigation. Thus, interviews were carried out with representative people of organizations of this productive category, as well as with some representatives of the local public authorities. So, some quizzes were applied to 35 irrigating small farmers to fulfill this research, with qualitative and quantitative questions. The interviews were made discursively, explaining the actions and difficulties of the organizational and institutional environments which are pro-irrigating family farming. The questionnaire data were partially worked in this first stage of the study using the descriptive statistics of the presented data. The results showed that public policies, driven by the institutions, have corroborated the permanence of this economic and social agent in the farm. However, the representative organizations work individually, without synchronization regarding the category needs. On the other hand, there can be seen the universities that are contrary to the other studied organizations, which seemed to be solid disseminators of irrigation technology locally. Secondly, the analysis identified the best statistical method that could present a similarity pattern among the listed socioeconomic variables, aiming to explain the irrigation impact on familiar farm agriculture of this municipality. Multivariate analysis was used by the main component analysis and cluster analysis method. PCA reduced the number from 23 to 8 components, while CP1 was the only one that selected most of the relevant variables, making the other part of the analysis difficult. When the principal components of the studied cases were identified, the PCA technique was not effective because some relevant information was lost to the study. The Cluster Analysis technique showed satisfactory results, when grouping the variables into four groups with high similarities among themselves. By grouping the cases, three groups were obtained that defined the irrigating farmers’ profile in Salto do Lontra. Three profiles were obtained: technified, reasonably technified and poorly technified. The technified ones have the highest percentage of irrigated area, higher education level, age from 45 to 53 years old, higher investments in technology, as well as increased life quality and satisfaction with irrigation application.